2001
DOI: 10.1093/condor/103.4.767
|View full text |Cite
|
Sign up to set email alerts
|

Annual Patterns of Molt and Reproductive Activity of Passerines in South-Central Brazil

Abstract: We analyzed the occurrence of molt and brood patches in resident passerines from four localities in south-central Brazil. The annual patterns of molt and reproductive activity were very similar among the sites. Brood patches first appeared in August, but were most common between October and January, with a peak in November, early in the rainy season. Molt started in October but was most widespread from the middle to the end of the rainy season, between December and April with a peak in February. Timing of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
2
9
0
8
Order By: Relevance
“…Clutch sizes were also three eggs for the nests found in Tobago (n = 3 nests) (Ffrench, 2012) and in Minas Gerais state (n = 2 nests) (Lopes et al 2013), while two nests found in southern Brazil contained only one well-develop young each (Belton, 1985), matching our observation that only one nestling fledged. Breeding activities were recorded on November in southeastern and southern Brazil (Belton, 1985;Lopes et al 2013), which together with our nest found in October, is within the breeding season range expected for most passerine birds from these regions (Belton, 1985;Marini and Durães, 2001). Following the pattern of other widely distributed taxa, breeding season in northern South America was remarkably different (see also Davanço et al 2013;Perrella et al 2017;Nunes et al 2020), with nesting activities being recorded in February, April, May, and June in Tobago (Ffrench, 2012), although the number of studied nests is still not sufficient for precise breeding phenology determination.…”
supporting
confidence: 80%
“…Clutch sizes were also three eggs for the nests found in Tobago (n = 3 nests) (Ffrench, 2012) and in Minas Gerais state (n = 2 nests) (Lopes et al 2013), while two nests found in southern Brazil contained only one well-develop young each (Belton, 1985), matching our observation that only one nestling fledged. Breeding activities were recorded on November in southeastern and southern Brazil (Belton, 1985;Lopes et al 2013), which together with our nest found in October, is within the breeding season range expected for most passerine birds from these regions (Belton, 1985;Marini and Durães, 2001). Following the pattern of other widely distributed taxa, breeding season in northern South America was remarkably different (see also Davanço et al 2013;Perrella et al 2017;Nunes et al 2020), with nesting activities being recorded in February, April, May, and June in Tobago (Ffrench, 2012), although the number of studied nests is still not sufficient for precise breeding phenology determination.…”
supporting
confidence: 80%
“…A espécie reproduziu a partir do final da estação seca, início do período chuvoso (outubro-dezembro). Vários autores têm registrado semelhante padrão para diferentes espécies neotropicais (Aguilar et al, 1999;Oniki & Willis, 1999;Piratelli et al, 2000;Marini & Durães, 2001;Duca & Marini, 2004;Lopes & Marini, 2005a;Medeiros & Marini, 2007;Faria et al, 2008;Rubio & Pinho, 2008;Marini et al, 2009aMarini et al, , 2009bHoffmann & Rodrigues, 2011). A estação reprodutiva é determinada por um conjunto de fatores, particularmente a disponibilidade de alimento (Hau, 2001;Wikelski et al, 2000;Boulton et al, 2011).…”
Section: Discussionunclassified
“…O início do período reprodutivo de S. islerorum coincide com o princípio da temporada reprodutiva da maioria dos Passeriformes na região sudeste e centro-oeste do Brasil (Piratelli, 1999;Marini & Durães, 2001). A atividade reprodutiva de S. islerorum durante o mês de setembro também é registrada por Zimmer et al, (2001) no estado do Mato Grosso, tendo os 10 indivíduos por ele coletados apresentado gônadas desenvolvidas.…”
Section: Discussionunclassified